Privacy Act; Proposed New Systems of Records, Single Family Mortgage Asset Recovery Technology (SMART/A80H) (The Federal Register / FIND, 2008)
Establishment of a new Privacy Act System of Records. Citation: "73 FR 41105" Document Number: "Docket No. FR-5130-N-26" Page Number: "41105" "Notices" SUMMARY: The Department of Housing and Urban Development HUD proposes to establish a new record system to add to its inventory of systems of records subject to the Privacy Act of 1974 (5 U.S.C. 552a), as amended. The proposed new system of record is the Single Family Mortgage Asset Recovery Technology (SMART). The SMART system will be used for accounting level detail on forward and reverse mortgages; case-tracking ability; report generating capability; query functions; database management, analyzing, processing, and tracking for FHA Insured and Secretary-held first, second and subordinate note and mortgage loan servicing functions.